Swallowing these drugs every day, you get tired”: a mixed-methods study to identify Barriers and facilitators to retention and HIV Viral Load suppression among the Adolescents living with HIV in TASO Mbale and TASO Soroti centers of excellence - Oryokot, Bonniface; Kazibwe, Andrew; Oluka, Abraham Ignatius; Kagimu, David; Bakashaba, Baker; Ssentongo, Saadick; Mafabi, Twaha; Odoi, Charles; Kawuba, Abubaker; Miya, Yunus; Etukoit, Bernard Michael; Mugisha, Kenneth; et al. (Research Square, 2023)
Background Adolescents aged 10–19, living with HIV (ALHIV) lag behind in attaining optimal viral load suppression (VLS) rates and retention in care, an important impediment to reaching epidemic control. This study aimed to identify barriers and facilitators to both VLS and retention among in the sub-population who seek care from TASO Mbale and TASO Soroti centers of excellence, to facilitate adaptation of the operation triple zero in the setting. Methods We used a mixed methods approach, extracting secondary data on ALHIV who were active in care during April-June 2022 quarter to determine one year retention in care. Analysis was done in STATA Corp, 15.0. We used logistic regression to determine associated factors and adjusted odds ratio (aOR) to report level of predictability, using 95% confidence interval (CI) and P<0.05 for statistical significance. For qualitative component, purposive sampling of 59 respondents was done. Focused group discussions, key informant interviews, and in-depth interviews were used to collect data. Thematic content analysis was done using Atlas ti. Results There were 533 ALHIV, with 12-month retention rate of 95.9% and VLS rate of 74.9%. Predictors for good VLS included good adherence [aOR:95%CI 0.066(0.0115, 0.38) P=0.02], being on first line treatment [aOR:95%CI 0.242 (0.0873,0.6724) P=0.006]. For retention, they include being a school going [aOR:95%CI 0.148(0.024,0.9218) P=0.041], multi month dispensing aOR:95%CI 32.6287(5.1446,206.9404) P<0.001, OVC enrolment aOR:95%CI 0.2625(0.083, 0.83) P=0.023]. Meanwhile key barriers included: individual ones such as internal stigma, lack of transport and treatment/drug fatigue; facility-level such as prolonged waiting time and lack of social activities; community level include stigma and discrimination, inadequate social support and food shortage. In terms of facilitators, individual level ones include good adherence and knowledge of one’s HIV status; facility-level such as provision of adolescent friendly services and community-level such as social support and decent nutrition. Conclusions VLS rate was sub-optimal mainly due to poor adherence. HIV programs could utilize the barriers and facilitators identified to improve VLS. Conversely, retention rate at one year was good, likely due to provision of adolescent friendly health services. ALHIV and their caregivers need to be empowered to sustain retention and improve VLS.